The Relationship between Cobalt Amount and Oxidation Parameters in NiTiCo Shape Memory Alloys - Mohammed, S. S.; Kok, M.; Cirak, Z. D.; Qader, I. N.; Dagdelen, F.; Zardawi, H. S. A. (Pleiades Publishing Ltd, 2020)
Coating shape-memory alloys (SMAs) with a ceramic layer is an important way by which metallurgists change some physical properties and improve biocompatibilities of (SMAs) for some medical purposes. The oxidation behaviors of five NiTiCo samples with different compositions were investigated and their influence on the thermal characteristics of phase transformation temperatures was studied. The kinetic oxidation as a function of time was determined by using the results of measurements via a combined method of the thermal gravimetrical (TG) and differential thermal (DT) analysis (TG/DTA), at 1323 K for one hour. The SEM-EDX results showed that an oxidation layer covered the surface of the alloys with ceramic compounds consisting of titanium and oxygen. The phase transformation temperatures were increased with respect to non-oxidized NiTiCo alloys. Likewise, the enthalpy change during the heating process was affected by the oxidation process.
Keywords: shape memory alloy; cobalt; oxidation; NiTi-based shape memory alloy